Metabolic Pathway of Topramezone in Multiple-Resistant Waterhemp (Amaranthus tuberculatus) Differs From Naturally Tolerant Maize - Lygin, Anatoli V.; Kaundun, Shiv S.; Morris, James A.; Mcindoe, Eddie; Hamilton, Andrea R.; Riechers, Dean E. (Frontiers in Plant Science, 2018)
Waterhemp [Amaranthus tuberculatus (Moq.) Sauer] is a problematic dicot weed in maize, soybean, and cotton production in the United States. Waterhemp has evolved resistance to several commercial herbicides that inhibit the 4-hydroxyphenylpyruvate-dioxygenase (HPPD) enzyme in sensitive dicots, and research to date has shown that HPPD-inhibitor resistance is conferred by rapid oxidative metabolism of the parent compound in resistant populations. Mesotrione and tembotrione (both triketones) have been used exclusively to study HPPD-inhibitor resistance mechanisms in waterhemp and a related species, Amaranthus palmeri (S. Wats.), but the commercial HPPD inhibitor topramezone (a pyrazolone) has not been investigated from a mechanistic standpoint despite numerous reports of cross resistance in the field and greenhouse. The first objective of our research was to determine if two multiple herbicide-resistant (MHR) waterhemp populations (named NEB and SIR) metabolize topramezone more rapidly than two HPPD inhibitor-sensitive waterhemp populations (named SEN and ACR). Our second objective was to determine if initial topramezone metabolite(s) detected in MHR waterhemp are qualitatively different than those formed in maize. An excised leaf assay and whole-plant study investigated initial rates of topramezone metabolism (< 24 hr) and identified topramezone metabolites at 48 hours after treatment (HAT), respectively, in the four waterhemp populations and maize. Results indicated both MHR waterhemp populations metabolized more topramezone than the sensitive (SEN) population at 6 HAT, while only the SIR population metabolized more topramezone than SEN at 24 HAT. Maize metabolized more topramezone than any waterhemp population at each time point examined. LC-MS analysis of topramezone metabolites at 48 HAT showed maize primarily formed desmethyl and benzoic acid metabolites, as expected based on published reports, whereas SIR formed two putative hydroxylated metabolites. Subsequent LC-MS/MS analyses identified both hydroxytopramezone metabolites in SIR as different hydroxylation products of the isoxazole ring, which were also present in maize 48 HAT but at very low levels. These results indicate that SIR initially metabolizes and detoxifies topramezone in a different manner than tolerant maize.